The role of protein p16(INK4a) in glottic laryngeal squamous cell carcinoma - Kalfert, David; Celakovsky, Petr; Laco, Jan; Ludvikova, Marie (Pathology oncology research, 2014)
Head and neck squamous cell cancer (HNSCC) includes tumors of various anatomical sites sharing the common etiological factors. However some differences in pathogenesis and prognosis of HNSCC have been hitherto documented. Laryngeal squamous cell carcinoma (LSCC) is one the most common type of the head and neck cancer. The majority of laryngeal cancers are located in the glottic area. P16 was recently documented to be important prognostic marker in many tumors including HNSCC. The aim of our study was to assess the significance of p16 expression in glottic LSCC. Fifty eight patients after surgical treatment of the glottic LSCC were enrolled in the retrospective study. The p16 expression was immunohistochemically detected and semiquantitatively evaluated in tumor tissue. The results were statistically correlated with clinical and pathological parameters. Protein p16 was expressed in glottic LSCC of 15 patients (25.9 %). Statistically significant higher p16 overexpression was proven in non-smokers in comparison with smokers (75 % versus 18 %; p =0.003). Recurrent cancer was diagnosed in 8 patients (13.8 %), and all these tumors were p16 negative. Our study shows, that p16 expression in glottic LSCC especially in subgroup of non-smokers might be promising prognosticator of better clinical outcome in routine practice. The p16 status did not statistically correlate with cervical lymph node metastases or with grading and staging of cancers, respectively. The preliminary results suggest that p16 overexpression in glottic LSCC may identify patients at low risk of disease recurrence. However, the pathobiology of this tumor as well as predictive role of p16 expression in laryngeal cancer still remains to be better elucidated.
Keywords: nádorové biomarkery; Follow-Up Studies; retrospektivní studie; Biomarkers, Tumor; Neoplasm Staging; Humans; lidé; Retrospective Studies; následné studie; lymfatické metastázy; lidé středního věku; míra přežití; spinocelulární karcinom; staging nádorů; Middle Aged; Lymphatic Metastasis; Female; Male; Laryngeal Neoplasms; Adult; prognóza; stupeň nádoru; Glottis; Prognosis; mužské pohlaví; Aged; Neoplasm Grading; Survival Rate; nádory hrtanu; ženské pohlaví; Carcinoma, Squamous Cell; glottis; lokální recidiva nádoru; dospělí; Cyclin-Dependent Kinase Inhibitor p16; inhibitor p16 cyklin-dependentní kinasy; Neoplasm Recurrence, Local; senioři